SYMBOLS OF POWER IN TRADITIONAL ARABIC DRESS: A SEMIOTIC STUDY OF CHARLES SANDERS PEIRCE - Saputri, Wiwil; Ilham, Muhammad (Journal of Language and Literature, 2023)
This article aims to find out the types of traditional Arab clothing in the Middle East and to find out the influence of symbols of power in traditional clothing in the lives of Arab society itself. Data was taken using Charles Sanders Peirce's semiotic theoretical approach. According to the findings, this research analyses the symbols of power in traditional Arab clothing. The results found that: first, the types of traditional Arab clothing have various variations. Arabs often use kaftans as their traditional clothing. This style of clothing has a loose, long cut and dates back to Ancient Persia; secondly, symbols of power in traditional Arab clothing symbolize status or caste in everyday life. Apart from that, these clothes also symbolize people who have a cultured personality and high dignity. As traditional clothing for Arab women, it has experienced fashion dynamics from time to time. The national clothing symbolizing Arab women presented in the fashion show was able to convey a contemporary impression but did not leave behind a legacy. Thus, traditional Arab clothing also provides a symbol of Arab society itself.